2015
DOI: 10.1016/j.sbspro.2015.06.361
|View full text |Cite
|
Sign up to set email alerts
|

SME Firm Performance-Financial Innovation and Challenges

Abstract: The paper begins with the theoretical analysis of the new economic norm, then analyses the changes on the financial report of SME enterprises in China under the new economic norm. And based on the analysis on the reasons of change on the financial report of SME enterprises in China under the new economic norm, it purposes the improvement of financial reporting in the current economic background of SEM enterprises. Finally, it summarizes the conclusion of this article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
124
0
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 130 publications
(137 citation statements)
references
References 15 publications
6
124
0
7
Order By: Relevance
“…The study therefore argues that lack of policy awareness will affect SMEs investment decisions. Hence, the hypothesis is formulated as, H4 = Lack of policy awareness will relate negatively to SMEs WTI External Financing: There are many research works (Rupeika-Apoga, 2014;Zidana, 2014;Prempeh, 2015;Eniola & Entebang, 2015;Preprah, 2016;Waked, 2016;Wang, 2016;Haron & Ibrahim, 2016) that had reported on challenges facing SMEs access external funding. Rupeika-Apoga (2014) investigated challenges within SMEs financing for three Baltic States and equipped the government and other stakeholders with instruments to comprehend SMEs' financing needs.…”
Section: Inadequate Credit Facilitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The study therefore argues that lack of policy awareness will affect SMEs investment decisions. Hence, the hypothesis is formulated as, H4 = Lack of policy awareness will relate negatively to SMEs WTI External Financing: There are many research works (Rupeika-Apoga, 2014;Zidana, 2014;Prempeh, 2015;Eniola & Entebang, 2015;Preprah, 2016;Waked, 2016;Wang, 2016;Haron & Ibrahim, 2016) that had reported on challenges facing SMEs access external funding. Rupeika-Apoga (2014) investigated challenges within SMEs financing for three Baltic States and equipped the government and other stakeholders with instruments to comprehend SMEs' financing needs.…”
Section: Inadequate Credit Facilitiesmentioning
confidence: 99%
“…Furthermore, the study showed that highly grown firms regard finance as the largest barrier to growth, and this manifests the popular beliefs that high growth firms exhibit higher demand for funds compared to feeble growth firms. In Nigeria, Eniola and Entebang (2015), sought to shed light on the sources of finance for SMEs, analyzed the difficulties in getting finance for SMEs with the purpose of employing innovative approaches to increase credit facilities. The study recommended that for SMEs in the country to become critical and indispensable to the national development, innovative systems must be employed to increase SMEs' access to finance through crowd funding.…”
Section: Inadequate Credit Facilitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Entrepreneur-firm performance is sine qua non to the performance of the country (Eniola & Entebang, 2015c). This implies entrepreneur-firm fills in as an underlying wellspring of inspiration for economic power.…”
Section: Introductionmentioning
confidence: 99%
“…In any case, remembering the true objective to begin or create business venture, the fund is fundamental. Consequently, company's manageability and achievement rely on upon a selection of financing choices (Eniola & Entebang, 2015c). For the requirements of this review, it will thus be basic to get a handle on; be that as it may, these decisions direct the organizations which were examined.…”
Section: Introductionmentioning
confidence: 99%